Analysis Of Idx 30 Stock Portfolio Performance During Covid 19 Pandemic - Anastasia Putri, Juan; Susanti, Elly; Tridianty Sianipar, Ruth (Publisher Cv. Inara, 2022)
Investors need to do proper analysis before making a decision in investing. If the investor does not do the right analysis, the investor will experience significant losses. One of the analyzes used is CAPM, and for the next step the researcher evaluates the performance of the stock portfolio. This study aims to analyze the performance evaluation of stock portfolios during the covid 19 pandemic. The research objects were companies registered in IDX 30 during the period January 2020 to July 2022. The result of this study is the Treynor index is the most indicative of conformity without differences between the three measures, as Treynor. Its value is similar to Sharpe and the Jensen index has the smallest difference.